Supplementing Yucca schidigera extract to mitigate frothy bloat in beef cattle receiving a high-concentrate diet. (7th November 2020) - Rett, Bruna; Cooke, Reinaldo F; Brandão, Alice P; Ferreira, Vitor S M; Colombo, Eduardo A; Wiegand, Jacob B; Pohler, Ky G; Rincker, Michael J; Schubach, Kelsey M
Abstract: This experiment compared incidence of frothy bloat, as well as ruminal, physiological, and performance responses of beef heifers receiving a bloat-provoking diet and supplemented with Yucca schidigera extract. Sixteen ruminally cannulated Angus-influenced heifers were ranked by body weight (BW ) and assigned to 4 groups of 4 heifers each. Groups were enrolled in a replicated 4 × 4 Latin square design containing 4 periods of 28 d, and a 21-d washout interval between periods. Groups were assigned to receive no Y. schidigera extract (CON ), or Y. schidigera extract at (as-fed basis) 1 g/heifer daily (YS1 ), 2 g/heifer daily (YS2 ), or 4 g/heifer daily (YS4 ). During each period, heifers ( n = 16/treatment) were housed in individual pens, and fed a sorghum ( Sorghum bicolor L.)-based bloat-provocative diet at 2% of their BW. Diet and treatments were individually fed to heifers, twice daily in equal proportions (0700 and 1600 hours). Heifers were assessed for bloat score (0 to 5 scale, increasing according to bloat severity) 3 hr after the morning feeding. Blood samples were collected on days 0, 7, 14, 21, and 28 prior to (0 hr) and at 3, 6, and 9 hr relative to the morning feeding. Rumen fluid samples were collected at the same time points on days 0 and 28. Orthogonal contrasts were tested to determine whether inclusion of Y. schidigera extract (0, 1, 2, or 4 g/heifer daily) yielded linear or quadratic effects, and explore an overall effect of Y. schidigera extract supplementation (CON vs. YS1 + YS2 + YS4). Rumen fluid viscosity was impacted quadratically by Y. schidigera extract inclusion ( P = 0.02), being greatest in YS1, followed by YS2, and equivalent between CON and YS4 heifers. Heifers receiving Y. schidigera extract had greater ( P ≤ 0.05) rumen propionate, iso-valerate, and valerate concentrations, as well as less ( P < 0.01) acetate : propionate ratio compared with CON heifers. Inclusion of Y. schidigera extract linearly increased ( P ≤ 0.04) average daily gain and feed efficiency. No other treatment effects were noted ( P ≥ 0.19) including bloat score (1.07 ± 0.03 across treatments), ruminal protozoa count, plasma concentrations of cortisol, haptoglobin, urea N, total protein, and rumen concentration of total volatile fatty acids. Supplementing Y. schidigera extract up to 4 g/d favored rumen propionate concentrations and linearly increased growth and feed efficiency but failed to mitigate incidence of frothy bloat in beef heifers consuming a grain-based bloat-provocative diet.